2015
DOI: 10.1097/phh.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Use of Evidence-Based Practices and Resources Among Comprehensive Cancer Control Programs

Abstract: Context While efforts to promote use of evidence-based practices (EBPs) for cancer control have increased, questions remain whether this will result in widespread adoption of EBPs (eg, Guide to Community Preventive Services interventions) by comprehensive cancer control (CCC) programs. Objective To examine use of EBPs among CCC programs to develop cancer control plans and select interventions. Design Conducted Web-based surveys of and telephone interviews with CCC program staff between March and July 2012.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…CDC promotes EBI use for all three of its cancer prevention and control programs: the NBCCEDP, the Colorectal Cancer Control Program (CRCCP), and the National Comprehensive Cancer Control Program (NCCCP). 2021 ensuring that grantees invest in programs that have proven effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDC promotes EBI use for all three of its cancer prevention and control programs: the NBCCEDP, the Colorectal Cancer Control Program (CRCCP), and the National Comprehensive Cancer Control Program (NCCCP). 2021 ensuring that grantees invest in programs that have proven effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, colleagues with the NCCCP found that limited resources and the lack of skills to adapt EBIs for local use, including adapting EBIs for cultural appropriateness, were central challenges for EBI use. 20 …”
Section: Discussionmentioning
confidence: 99%
“…28 To aid NCCCP programs and their coalitions with evaluation efforts, a domain in which results from performance measures indicate an area that needs improvement, an evaluation toolkit and cancer plan index planning tool have been developed and disseminated. 29 These tools were used by one NCCCP program to successfully conduct an outcome evaluation of their cancer plan, 30 and their findings may be used to refine future cancer plan implementation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…[23]), all provide EBI resources and tools for NCCCP participants [20]. A 2012 survey showed that 75% of NCCCP directors from states, tribes and/or USAPIJs reported using EBIs to address cancer plan objectives [24]. Most directors had used web sites for The Community Guide (95%) and Cancer Control P.L.A.N.E.T.…”
Section: Evidence For Initiatives and Interventionsmentioning
confidence: 99%
“…Most directors had used web sites for The Community Guide (95%) and Cancer Control P.L.A.N.E.T. (75%) [24]. Brief descriptions and specific examples of the types of activities are described below, categorized by each cancer continuum-related NCCCP priority area.…”
Section: Evidence For Initiatives and Interventionsmentioning
confidence: 99%